2008
DOI: 10.1111/j.1095-8312.2008.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

It is all in the head: morphological basis for differences in bite force among colour morphs of the Dalmatian wall lizard

Abstract: Males of the lizard Podarcis melisellensis occur in three distinct colours that differ in bite performance, with orange males biting harder than white or yellow ones. Differences in bite force among colour morphs are best explained by differences in head height, suggesting underlying variation in cranial shape and/or the size of the jaw adductors. To explore this issue further, we examined variation in cranial shape, using geometric morphometric techniques. Additionally, we quantified differences in jaw adduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 31 publications
(39 reference statements)
4
69
0
Order By: Relevance
“…PCSA calculations confirm this: male attachment surfaces are more than twice as large as those of females, theoretically enabling more than twice as much force production. This is comparable to the finding of enlarged jaw adductor musculature in Anolis and Podarcis lizards, causing elevated bite force performance (Herrel et al, 1995;Herrel et al, 2007;Huyghe et al, 2009). Despite the hypertrophy of the male stag beetle adductor muscles, they remain well aligned with the optimal direction.…”
Section: Research Articlesupporting
confidence: 79%
“…PCSA calculations confirm this: male attachment surfaces are more than twice as large as those of females, theoretically enabling more than twice as much force production. This is comparable to the finding of enlarged jaw adductor musculature in Anolis and Podarcis lizards, causing elevated bite force performance (Herrel et al, 1995;Herrel et al, 2007;Huyghe et al, 2009). Despite the hypertrophy of the male stag beetle adductor muscles, they remain well aligned with the optimal direction.…”
Section: Research Articlesupporting
confidence: 79%
“…This, together with the variation of allometric slopes observed among closely related species (Ljubisavljević et al, 2010) and the complete lack of head shape dimorphism observed in some instances (MonTEIro & Abe, 1997), indicates that important variation may exist across species, urging for further investigation. A promising line of research may be the elucidation of the functional significance of head shape SD as captured by GM methods, in order to provide further evidence to the long-standing hypothesis of sexual selection acting on bite force as the main determinant of the observed morphological patterns (HErrEL et al, 2007;HUyGHE et al, 2009;kALIonTzopoULoU et al, in press). …”
Section: Sexual Dimorphismmentioning
confidence: 99%
“…The shallow angle of the premaxillary notch and associated elongate tomiodonts in male C. p. marginata would be expected to produce a high bite force while exhibiting low levels of work and strain (Anderson and LaBarbera 2008). Other cranial modifications in male C. p. marginata, such as jaw length and/or associated muscles, may result in modified bite performance between the sexes, as documented with cranial dimorphism in lacertid lizards (Herrel et al 1996;Ljubisavljević et al 2008;Huyghe et al 2009). Differential bite performance between the sexes, owing to cranial and tomiodont dimorphism, implies ecological and/or sexual selection mechanisms underpinning the dimorphism.…”
Section: Functional and Practical Significance Of C Picta Tomiodont mentioning
confidence: 98%